PEMBAGIAN WARISAN PADA MASYARAKAT ADAT BATAK TOBA DESA SUNGAI KERJAN PROVINSI JAMBI - Manik, Herlina; Triadi Manurung, Antonus Anto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: This study aims (1) to find out and analyze the implementation of inheritance distribution to the Toba Batak Indigenous People in Sungai Kerjan Village, Bungo Regency, Jambi Province; (2) To find out and analyze the factors that influence changes in the process of dividing the Toba Batak customary heritage in Sungai Kerjan Village, Bungo Regency, Jambi Province. This research is descriptive analysis with the type of Juridical Empirical research, which uses primary data sources and secondary data. Primary data collection techniques through observation and interviews with customary leaders and those who have carried out inheritance. Secondary data collection techniques through library research. The discussion of this research is the daughters of the Toba Batak indigenous people in Sungai Kerjan Village who receive inheritance. The results of this study are that inheritance in the Toba Batak Indigenous People in Sungai Kerjan Village has experienced a change in inheritance where daughters get a share of the inheritance. This change is caused by several factors, namely: the factor of justice, the factor of religion, and the factor of compassion.Keywords: Traditional Heritage, Toba Batak, Batak Women